2016
DOI: 10.22323/2.15040202
|View full text |Cite
|
Sign up to set email alerts
|

Typologies of the popular science web video

Abstract: This article provides a first statistical analysis of the typologies and characteristics of popular science web videos on YouTube. An analysis of 190 videos from 95 online video channels was conducted. Several factors such as narrative strategies, video editing techniques, and design tendencies with regard to cinematography, the number of shots, the kind of montage used, and even the use of sound design and special FX point to a notable professionalism among science communicators independent of institutional o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 1 publication
2
62
1
3
Order By: Relevance
“…In this way, our classification corroborates the conclusions reached in similar studies on the existence of a wide variety of genres and subgenres [Muñoz Morcillo, Czurda and Robertson-von Trotha, 2016;Burgess and Green, 2013]. These different formats have then been classified into two groups, according to the channel for which they were intended, with the aim of establishing their fundamental differences.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this way, our classification corroborates the conclusions reached in similar studies on the existence of a wide variety of genres and subgenres [Muñoz Morcillo, Czurda and Robertson-von Trotha, 2016;Burgess and Green, 2013]. These different formats have then been classified into two groups, according to the channel for which they were intended, with the aim of establishing their fundamental differences.…”
Section: Discussionsupporting
confidence: 86%
“…However, if the capacities of the Internet are to be fully taken advantage of, the messages should be adapted to its requirements and include elements that foster interaction with the user; something that, as has been demonstrated in this study, does not occur in all cases. This result is in contrast with those of Muñoz Morcillo, Czurda and Robertson-von Trotha [2016], which revealed that most videos analysed in their sample include typical elements that foster community building and allow for their dissemination. We believe that the differences in the results are due to the difference between the two samples.…”
Section: Discussioncontrasting
confidence: 70%
“…Science communication on YouTube is getting increasingly professional. Also science communicators independent of institutional or personal commitments are applying progressively higher standards, for instance concerning aesthetics, and production quality (Muñoz Morcillo et al, 2016). Some science YouTubers, such as Veritasium 5 , VSauce 6 , or SciShow 7 for instance, reach many million viewers on YouTube and also have millions of subscribers to their video channels (Geipel, 2017(Geipel, , 2018.…”
Section: Science and Environmental Communication On Youtubementioning
confidence: 99%
“…The internet and YouTube are obvious choices for investigating gender issues in science education. YouTube contains many different types of science-related videos, including many that are documentary, recreational and educational (Erviti & Stengler, 2016;Muñoz Morcillo, Czurda, & Trotha, 2016). It is widely used in school classrooms and by university students to support learning (e.g., Barry, Marzouk, Chulak-Oglu, Bennett, Tierney, & O'Keeffe, 2016;Tan & Pearce, 2012) as well as for leisure-time explorations of science related content, such as by watching TED Talks videos (see below) or science-related music videos (Allgaier, 2013).…”
Section: Introductionmentioning
confidence: 99%